2022
DOI: 10.1108/ijpsm-12-2021-0263
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adaptability and its impact on the change readiness of civil servants

Abstract: PurposeUnderpinned by Social Cognitive Theory (SCT), this study aimed to examine the mediating role of employees' adaptability in the relationship between the five managerial climate factors (i.e., trust, supportiveness, openness, clarity of goals and participative) and change readiness in public sector organisations.Design/methodology/approachAdopting the quantitative approach, data were collected from 379 administrative and diplomatic officers. Analysis was done using partial least squares structural equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
(153 reference statements)
2
9
0
Order By: Relevance
“…In doing so, they attempt to meet the expectations of collective citizens for public value (Almazrouei et al, 2023). Indeed, the concern for creating public value by public sector organisations is increasingly gaining attention in the public sector literature as it is argued to be the goal of public sector organisations (Twizeyimana and Andersson, 2019;Yean et al, 2022). The need to create public value necessitates innovation because it improves public service quality, citizen satisfaction and the performance and efficiency of public organisations (Bryson et al, 2014;De Vries et al, 2016;Crosby et al, 2017;Panagiotopoulos et al, 2019).…”
Section: Fostering Innovative Behavioursmentioning
confidence: 99%
“…In doing so, they attempt to meet the expectations of collective citizens for public value (Almazrouei et al, 2023). Indeed, the concern for creating public value by public sector organisations is increasingly gaining attention in the public sector literature as it is argued to be the goal of public sector organisations (Twizeyimana and Andersson, 2019;Yean et al, 2022). The need to create public value necessitates innovation because it improves public service quality, citizen satisfaction and the performance and efficiency of public organisations (Bryson et al, 2014;De Vries et al, 2016;Crosby et al, 2017;Panagiotopoulos et al, 2019).…”
Section: Fostering Innovative Behavioursmentioning
confidence: 99%
“…There is a considerable amount of literature and research that identifies various factors that can influence employee change readiness, including [1] communication (Endrejat et al, 2021;Neill, Men, & Yue, 2019;Schulz-Knappe, Koch, & Beckert, 2019), [2] leadership (Gelaidan et al, 2018;Indriastuti & Fachrunnisa, 2021;Islam, Furuoka, & Idris, 2021b, 2021a organizational culture (Olafsen, Nilsen, Smedsrud, & Kamaric, 2021;Samal, Patra, & Chatterjee, 2021;Trisnanto & Soetjipto, 2022;Wong, 2021), [4] organizational identification (Aitken & von Treuer, 2021;Hameed et al, 2019;Neill et al, 2019), and [5] change beliefs (Commer, Sci, Kashif Imran, Muhammad, & Iqbal, 2021;Hameed et al, 2019;Islam et al, 2021a;Mei Kin, Abdul Kareem, Nordin, & Wai Bing, 2018;Rafferty & Minbashian, 2019). Recently, Yean, et al (2022) attempted to identify other factors that may affect change readiness by conducting a study to examine the impact of several factors that are summarized as managerial climate, and adaptability on change readiness.…”
Section: Thementioning
confidence: 99%
“…Thus, the main objective of this study is to explore factors that drive change readiness in public sector organizations. To do this, we modify previous studies and build upon the factors identified by Hameed et al (2019) and Yean et al (2022), which will be explained below. Therefore, the research question of this study is "How do organizational identification and managerial climate affect employee change readiness, while taking into account adaptability as a mediator?…”
Section: Thementioning
confidence: 99%
See 2 more Smart Citations